2016
DOI: 10.3389/fmicb.2015.01569
|View full text |Cite
|
Sign up to set email alerts
|

Hanseniaspora uvarum from Winemaking Environments Show Spatial and Temporal Genetic Clustering

Abstract: Hanseniaspora uvarum is one of the most abundant yeast species found on grapes and in grape must, at least before the onset of alcoholic fermentation (AF) which is usually performed by Saccharomyces species. The aim of this study was to characterize the genetic and phenotypic variability within the H. uvarum species. One hundred and fifteen strains isolated from winemaking environments in different geographical origins were analyzed using 11 microsatellite markers and a subset of 47 strains were analyzed by AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 112 publications
(118 reference statements)
8
68
2
Order By: Relevance
“…pH has a significant impact on the fermentation, because it effects on the growth of yeasts, the fermentation rates and the formation of byproducts. So, maintenance of pH constant during fermentation is very important for the processes (Albertin et al, 2016). In accordance with our results, Pramanik (2003) reported that the maximum ethanol concentration produced by S. cerevisiae was achieved at pH 4.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…pH has a significant impact on the fermentation, because it effects on the growth of yeasts, the fermentation rates and the formation of byproducts. So, maintenance of pH constant during fermentation is very important for the processes (Albertin et al, 2016). In accordance with our results, Pramanik (2003) reported that the maximum ethanol concentration produced by S. cerevisiae was achieved at pH 4.…”
Section: Discussionsupporting
confidence: 90%
“…It seems that such yeast species will carry out much fermentation instead of S. cerevisiae in the future. Temperature is one of the most important factors affecting ethanol production is fermentation, which has a direct effect on the biochemical reactions of yeast (Albertin et al, 2014(Albertin et al, , 2016. Also, temperature is known to affect yeast metabolism and, as a result, the formation of some metabolites such as ethanol, glycerol, acetic acid (LafonLafourcade, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas was found in aboveground grape plants and could influence plant health and productivity in previous studies (Albertin et al . ; Garofalo et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…For all these species, at least two independent events of domestication were identified, indicating that anthropization drastically shapes the genetic diversity of these wine yeasts. Conversely, some wine yeast species like Hanseniaspora uvarum showed no impact of human processes (Albertin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae , where the vintage contributed less to the global genetic variation in close vintages (Börlin et al, ) but diverging from H . uvarum populations that show important genetic variation between vintages (Albertin et al, ). It is worth noting that the vintages analysed in this work (i.e., 2015 and 2017) had marked differences in climatic conditions.…”
Section: Discussionmentioning
confidence: 99%